Development of a standardized testing procedure for assessing the irritation potential of occupational skin cleansers - Elsner, Peter; Seyfarth, Florian; Antonov, Dimitar; John, Swen Malte; Diepgen, Thomas L.; Schliemann, Sibylle (Contact dermatitis, 2014)
Background Frequent skin cleaning fulfils the definition of occupational ‘wet work’. Standardized methods are required to assess the irritation potential of workplace cleansers. Objectives To develop a standardized procedure for testing the irritation potential of occupational skin cleansers. Methods In this single-blind, single-centre trial in 25 healthy volunteers, the irritation potential of five generic reference cleansers was tested by three-times-daily washing with an automated skin cleaning device for 4 days, and quantification of cumulative skin barrier damage was performed by visual scoring, chromametry, transepidermal water loss TEWL, and corneometry. For two cleansers, reproducibility of the irritancy assessment was assessed. Furthermore, the irritation induced by four commercial workplace skin cleansers was studied. Results Whereas no significant changes were observed for any of the tested cleansers by either visual scoring or chromametry, significant increases in TEWL and significant decreases in stratum corneum hydration were found for all cleansers. Cleansers differed significantly in their irritation potential. On retesting of two cleansers, the first results were confirmed. Among the four commercial cleansers, one that was claimed to be mild was found to be disproportionally irritant. Conclusions The presented model for testing cleansing preparations allows a highly controlled, practically relevant and reproducible irritancy assessment of occupational skin cleansers.